New Zealand Rabbit Spermatozoa Concentration after Giving of Beluntas Leaf Tannin Extract (Pluchea indica) - Susetyarini, Eko; Nurrohman, Endrik (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2022)
The purpose of this study was to determine the concentration of spermatozoa in New Zealand rabbits after giving of various types of beluntas leaf tannin extract. This type of research is experimental research. The research design is a one-group post-test design. A sample of 16 rabbits. The sampling technique used is purposive random sampling. The research was conducted at the Chemical Engineering Laboratory of the State Polytechnic of Malang, the Laboratory of Kesimma Medica Malang, the Integrated Laboratory, and the Biology Laboratory of the University of Muhammadiyah Malang. The study was carried out from August to September 2019. The study design used a completely randomized design (CRD) with 4 treatments, namely hydrolyzed, condensed, and pure tannin extract of beluntas leaves and the control group was given aquades orally with a dose of 3 ml/kgbb with 4 replications. repetition times. The procedure of this research 1) Preparation of extract of beluntas leaf tannins, 2) Phytochemical test of extract preparations, 3) Treatment of rabbits as experimental animals, 4) Surgery and collection of rabbit spermatozoa, 5) Observation of spermatozoa using a microscope, 6) Calculating the concentration of spermatozoa. The method of data collection was by calculating the concentration of spermatozoa in each treatment using a hemocytometer and a Neubauer counting chamber using a binocular microscope. Data analysis with one-way Anova test and Duncan 5%. The results showed that the dosage of 3ml/kgbb of various types of beluntas leaf tannin extract had an effect on the spermatozoa concentration of New Zealand rabbits (sig<0.05). The findings of this study are that the best treatment that can reduce the number of spermatozoa in New Zealand rabbits is the condensed tannin extract of Beluntas leaves.